TANGGUNG JAWAB SUAMI ATAS NAFKAH TERHADAP MANTAN ISTRI DAN ANAK PASCA PERCERAIAN MENURUT UNDANG-UNDANG PERKAWINAN DAN KOMPILASI HUKUM ISLAM - NOVITA MARASTI; Fatria Hikmatiar Al Qindy (Private Law, 2023)
The aim of this research is to examine the implementation of husband's responsibility for sustenance towards ex-wife and children in Mujur Village, East Praya Sub-District, Central Lombok Regency, and the obstacles in enforcing husband's responsibility for sustenance towards ex-wife and children. The research method used is normative-empirical research. The results of the research showed that: 1) Fulfillment of the right to maintenance of wife and children after divorce in Mujur Village, East Praya District, Central Lombok Regency, based on data obtained from an interview with Posbakum of the Praya Religious Court, Central Lombok, Researchers found various patterns for fulfilling the rights of the wife and child maintenance after divorce. There were several patterns in its implementation: some always provide, sometimes provide, once provide, and never provide. 2) The factors affecting the fulfillment of the biological father's responsibility for the wife's and children's sustenance after divorce, including where a biological father or ex-husband was unable to fulfill his obligations in providing his children's sustenance. In addition to internal factors, factors that were no less important in terms of fulfilling the biological father's responsibility for child support after divorce were external factors that could encourage, directly or indirectly, the community's understanding of the biological father's responsibility for child maintenance after divorce.